Fast-Response Fiber-Optic FPI Temperature Sensing System Based on Modulated Grating Y-Branch Tunable Laser - Yang Cheung; Zhenguo Jing; Qiang Liu; Ang Li; Yueying Liu; Yihang Guo; Sen Zhang; Dapeng Zhou; Wei Peng (Photonic Sensors)
Abstract In this paper, a cost-effective and miniaturized instrument is proposed, which is based on a tunable modulated grating Y-branch (MG-Y) laser for rapid temperature measurement using a Fabry-Perot interferometer (FPI) sensor. The FPI sensor with a 1 463-µm cavity length is a short segment of a capillary tube sandwiched by two sections of single-mode fibers (SMFs). This system has a broad tunable range (1 527 nm–1 567 nm) with a wavelength interval of 8 pm and a tuning rate of 100 Hz. Temperature sensing experiments are carried out to investigate the performance of the system by demodulating the absolute cavity length of the FPI sensor using a cross-correlation algorithm. Experimental results show that the sensor can reach the response time as short as 94 ms with the sensitivity of 802 pm/°C. Benefiting from the homemade and integrated essential electrical circuits, the entire system has the small size, low cost, and practical application potential to be used in the harsh environment for rapid temperature measurement.